2020
DOI: 10.1161/jaha.119.015289
|View full text |Cite
|
Sign up to set email alerts
|

Familial Recurrent Myocarditis Triggered by Exercise in Patients With a Truncating Variant of the Desmoplakin Gene

Abstract: Background Variants of the desmosomal protein desmoplakin are associated with arrhythmogenic cardiomyopathy, an important cause of ventricular arrhythmias in children and young adults. Disease penetrance of desmoplakin variants is incomplete and variant carriers may display noncardiac, dermatologic phenotypes. We describe a novel cardiac phenotype associated with a truncating desmoplakin variant, likely causing mechanical instability of myocardial desmosomes. Methods and Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 57 publications
0
58
0
1
Order By: Relevance
“…These forms are often diagnosed as acute myocarditis, thus underlying the poor diagnostic accuracy of classic ACM diagnostic criteria and the need for other diagnostic tools in such cases. Recurrent episodes of acute myocarditis among family members, or a personal history of acute myocarditis combined with a family history of cardiomyopathy or SCD, should raise the suspicion of LV variants of ACM, and tissue characterization and genetic testing should be advised [56,57].…”
Section: Desmosomal Mutationsmentioning
confidence: 99%
“…These forms are often diagnosed as acute myocarditis, thus underlying the poor diagnostic accuracy of classic ACM diagnostic criteria and the need for other diagnostic tools in such cases. Recurrent episodes of acute myocarditis among family members, or a personal history of acute myocarditis combined with a family history of cardiomyopathy or SCD, should raise the suspicion of LV variants of ACM, and tissue characterization and genetic testing should be advised [56,57].…”
Section: Desmosomal Mutationsmentioning
confidence: 99%
“…That is why perhaps cardiotropic viruses are more frequently identified in patients with AC than in control subjects. Interestingly, in patients with DSP mutation and recurrent myocarditis, intense physical activity has been described as another potential trigger, thus reinforcing the need to consider genomic-environment interaction [ 24 ].…”
Section: Genetic Involvement In the Clinical Presentation And Evolution Of Myocarditismentioning
confidence: 99%
“…Indeed, family history of cardiomyopathy, sudden cardiac death, and pacemaker implantation in early age may suggest the transmission of pathogenic genetic variants. Also, the recurrence of acute myocarditis has been recognized as a clear risk factor for underling genetic mutation [15,24]. Moreover, genetic predisposition to myocarditis is also supported by the presence of clinical traits at the physical examination (e.g., neurosensory disorders, skeletal muscle involvement, woolly hair, and keratoderma), at the laboratory analysis (e.g., creatine kinase elevation), at the ECG evaluation (e.g., persistent left bundle branch block, AV block, posterolateral pseudonecrosis, low voltage, epsilon wave), and at cardiac RMN (e.g., diffuse LGE).…”
Section: Ttn Truncating Variants: An Example Of the Interaction Between Genetics And Environmentmentioning
confidence: 99%
“…[ 56 ] In two young brothers with recurrent myocarditis triggered by physical exercise, screening of 218 cardiomyopathy-related genes revealed the presence of the heterozygous truncating variant p.Arg1458Ter in DSP. [ 57 ] Reichl et al [ 58 ] reported a case of a young male with acute myocarditis as the first presentation of DSP variant-associated ACM. FDG PET scans in four DSP cases revealed that acute LV myocardial injury is associated with myocardial inflammation, initially misdiagnosed as cardiac sarcoidosis or myocarditis.…”
Section: Dsp Cardiomyopathy Clinical Manifestationsmentioning
confidence: 99%